Practice Profile and Geographical Distribution of Ophthalmologists in the Philippines (Annals of Medicine and Medical Sciences, 2025)
Objectives: Determine practice profile, distribution, ophthalmology/population ratio (OPR), and density per region, and compare them based on the dimensions of eyecare services: availability, affordability, accessibility, and adequacy. Methods: A cross-sectional study of members and non-members of the Philippine Academy of Ophthalmology (PAO) from August to December 2022 using an online survey. Results: There were 1140 respondents, 636(58%) males. 979(86%) were actively practicing. 852(89%) hold only or predominantly private practice. 541(55%) were general ophthalmologists (GO). 134 respondents are still in training. Primary clinics were highest in the National Capital Region (NCR) (34%). 80% of all clinics of ophthalmologists are located in Luzon. Ophthalmologists held clinics in only 244(15%) municipalities/cities. 22% of municipalities/cities in Luzon, 9% in Visayas, and 8% in Mindanao had ophthalmologists. Conclusion: Almost all were seeing patients in practice or in training. Despite a slight male predominance, women ophthalmologists were >20-35% in Western countries. There was an increase in density to 15.6. NCR has the highest density (52.8), better than the United Kingdom (49) in 2012. Luzon had the highest density among the 3 major areas in the Philippines at 21.8, better than China’s 20 in 2016. Region 12 and the Bangsamoro Autonomous Region of Muslim Mindanao (BARMM) had low density.